Profile and crowding of currents in mesoscopic superconductors with an array of antidots - Okimoto, D. [UNESP]; Sardella, E. [UNESP]; Zadorosny, R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Studies with mesoscopic superconducting materials have made significant advances in the last decades. One of the applications of such systems is in devices for single-photon and single-electron detectors. However, depending on the geometry of these systems, crowding current effects take place, and as a consequence, the total critical current could decrease, which facilitates the penetration of vortices. This effect could be also responsible for a variety of penetration morphologies of flux avalanches in macroscopic samples. Thus, in this paper, we used the time-dependent Ginzburg-Landau theory to study the crowding current effects in mesoscopic superconducting systems with an array of antidots. It is demonstrated that the profile of the currents is influenced by the antidots, i.e., in the vertices of the antidots, the intensity of the currents increases and distinguishably presents profiles, which depends on the size of the systems. Thus, we demonstrate that the distance between the antidots influences the current crowding effect, and the fabrication of future devices should be thought in order to minimize such effect.
Keywords: antidots; crowding current; mesoscopic; TDGL